2021
DOI: 10.1111/eos.12802
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of rotary nickel‐titanium endodontic instruments: A critical review of the methodology

Abstract: Finite element analysis has been a valuable research tool for rotary nickel-titanium endodontic files over the last two decades. This review aims to summarise and critique the methodology as used in currently available endodontic literature for finite element analysis of rotary nickel-titanium instruments. An electronic literature research in PubMed and Scopus databases was performed using the appropriate search terms, and the titles and abstracts were screened for relevance. The review revealed an inconsisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Some previous studies have shown the predictive capacity of this simulated approach based on the use of FE models to predict the location of the file fracture [ 7 , 8 ]. However, a recent review highlighted some limitations introduced in previous FE studies in this field, especially in the representation of the boundary conditions, the accuracy of the mesh to represent the real file geometry or the lack of consideration of friction in the FE analysis [ 21 ]. Our investigation solved these main limitations, with a very accurate mesh of quadratic elements for the file, and undertook a transient non-linear simulation of the introduction of the file inside the root canal and its rotation inside the canal, including contact and friction simulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have shown the predictive capacity of this simulated approach based on the use of FE models to predict the location of the file fracture [ 7 , 8 ]. However, a recent review highlighted some limitations introduced in previous FE studies in this field, especially in the representation of the boundary conditions, the accuracy of the mesh to represent the real file geometry or the lack of consideration of friction in the FE analysis [ 21 ]. Our investigation solved these main limitations, with a very accurate mesh of quadratic elements for the file, and undertook a transient non-linear simulation of the introduction of the file inside the root canal and its rotation inside the canal, including contact and friction simulation.…”
Section: Discussionmentioning
confidence: 99%
“…This method allows gaining some insight into the stress and strain distributions inside the file, helping gain a better understanding of the failure mechanism. A recent study made a critical review of the use of this method applied to NiTi endodontic instruments [ 21 ] and highlighted some of the main limitations of the analyses performed to date. According to this study, very few studies modelled cyclic fatigue using FE simulation.…”
Section: Introductionmentioning
confidence: 99%
“…FEA has the ability to obtain the stress magnitude and direction of the interior of an object without destroying the sample (Richert et al, 2020). A task running on a three-dimensional model under a particular load usually takes no longer than 1 h. Though FEA often requires numerous job running and modifications of the models to get reliable results, it still consumes less time and cost compared with experimental research (Chien et al, 2021). In FEA, stress, strain, force and displacement could be evaluated through the analysis.…”
Section: Advantages Of Feamentioning
confidence: 99%
“…Recently, finite element analysis (FEA) has been explored as a tool to support and validate experimental findings from benchtop cyclic fatigue testing (Chien et al, 2021 ). FEA is a numerical analysis where a physical model is subdivided into smaller “finite” elements to form a mesh model, which can then be investigated via computational algorithms to establish the relationships between these elements (Chien et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, finite element analysis (FEA) has been explored as a tool to support and validate experimental findings from benchtop cyclic fatigue testing (Chien et al, 2021 ). FEA is a numerical analysis where a physical model is subdivided into smaller “finite” elements to form a mesh model, which can then be investigated via computational algorithms to establish the relationships between these elements (Chien et al, 2021 ). Multiple studies have used FEA to visualize stresses within rotary NiTi instruments during the shaping of the root canal and to provide insight into their mechanical behavior (Arbab‐Chirani et al, 2011 ; Chien et al, 2023 ; Ha et al, 2015 ; Kim et al, 2008 , 2009 ; Lee et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%